Conjoint effect of mobile normal and torque loads on tunnel with circular support; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 1 - Ukrainets V. N. (Mathematics and mechanics. Physics, 2007)
Заглавие с титульного листа